2022
DOI: 10.1111/ecca.12422
|View full text |Cite
|
Sign up to set email alerts
|

Military Conscription, Sexist Attitudes and Intimate Partner Violence

Abstract: We provide empirical evidence on the long-term causal impact of military conscription on sexist attitudes and intimate partner violence. To address potential endogeneity, we exploit the conscription draft lottery in Argentina. We combine the draft administrative data with self-reported survey data. We find that conscription causes men to adopt more sexist attitudes in dimensions such as justification of sexism and violence, sexual machismo, negative attitude towards homosexuality, old-fashioned sexism, and hos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…Military service is legally available to women on equal terms as men in several Western democracies (Carreiras, 2006;Doan & Portillo, 2016;King, 2013;Mota et al, 2018;Muhr & Sløk-Andersen, 2017;Reis & Menezes, 2020;Winslow & Dunn, 2002). However, studies have found that the prevailing image of a soldier 1 remains masculine (Alchin et al, 2018;Boldry et al, 2001;Do & Samuels, 2021), and that soldiers can be socialized into sexist attitudes and behavior within the military (Gibbons & Rossi, 2022). Furthermore, integrating women into the military structurally does not automatically change these norms (Carreiras, 2006;Collins-Dogrul & Ulrich, 2018;Ette, 2013;Higate, 2003;King, 2015;Kvarving, 2019;Pendlebury, 2020;Welland, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Military service is legally available to women on equal terms as men in several Western democracies (Carreiras, 2006;Doan & Portillo, 2016;King, 2013;Mota et al, 2018;Muhr & Sløk-Andersen, 2017;Reis & Menezes, 2020;Winslow & Dunn, 2002). However, studies have found that the prevailing image of a soldier 1 remains masculine (Alchin et al, 2018;Boldry et al, 2001;Do & Samuels, 2021), and that soldiers can be socialized into sexist attitudes and behavior within the military (Gibbons & Rossi, 2022). Furthermore, integrating women into the military structurally does not automatically change these norms (Carreiras, 2006;Collins-Dogrul & Ulrich, 2018;Ette, 2013;Higate, 2003;King, 2015;Kvarving, 2019;Pendlebury, 2020;Welland, 2010).…”
Section: Introductionmentioning
confidence: 99%